Rapid and Accurate Campylobacter jejuni Detection With CRISPR-Cas12b Based on Newly Identified Campylobacter jejuni-Specific and -Conserved Genomic Signatures - Huang, Yu; Gu, Dan; Xue, Han; Yu, Jinyan; Tang, Yuanyue; Huang, Jinlin; Zhang, Yunzeng; Jiao, Xinan (Frontiers in Microbiology, 2021)
Campylobacter jejuni is among the most prevalent foodborne zoonotic pathogens leading to diarrheal diseases. In this study, we developed a CRISPR-Cas12b-based system to rapidly and accurately detect C. jejuni contamination. Identification of C. jejuni-specific and -conserved genomic signatures is a fundamental step in development of the detection system. By comparing C. jejuni genome sequences with those of the closely related C. coli, followed by comprehensive online BLAST searches, a 20 bp C. jejuni-conserved (identical in 1024 out of 1037 analyzed C. jejuni genome sequences) and -specific (no identical sequence detected in non-C. jejuni strains) sequence was identified and the system was then assembled. In further experiments strong green fluorescence was observed only when C. jejuni DNA was present in the system, highlighting the specificity of this system. The assay, with a sample-to-answer time of 40 min, positively detected chicken samples that were contaminated with a dose of approximately 10 CFU C. jejuni per gram chicken, which was >10 times more sensitive than the traditional Campylobacter isolation method, suggesting that this method shows promise for onsite C. jejuni detection. This study provides an example of bioinformatics-guided CRISPR-Cas12b-based detection system development for rapid and accurate onsite pathogen detection.